Interrelationship between serum and sputum inflammatory mediators in chronic obstructive pulmonary disease - Bizeto,L. (2008)
Little is known about airway inflammatory markers in chronic obstructive pulmonary disease (COPD). The objective of the present study was to identify and try to correlate pulmonary and peripheral blood inflammatory markers in COPD. In a cross-sectional study on patients with stable COPD, induced sputum and blood samples were collected for the determination of C-reactive protein, eosinophilic cationic protein, serum amyloid A protein, a-1 antitrypsin (a-1AT), and neutrophil elastase. Twenty-two patients were divided into two groups according to post-bronchodilator forced expiratory volume in the first second (%FEV1): group 1 (N = 12, FEV1 <40%) and group 2 (N = 10, FEV1 ³40%). An increase in serum elastase, eosinophilic cationic protein and a-1AT was observed in serum markers in both groups. Cytology revealed the same total number of cells in groups 1 and 2. There was a significantly higher number of neutrophils in group 1 compared to group 2 (P < 0.05). No difference in eosinophils or macrophages was observed between groups. Serum elastase was positively correlated with serum a-1AT (group 1, r = 0.81, P < 0.002 and group 2, r = 0.83, P < 0.17) and negatively correlated with FEV1 (r = -0.85, P < 0.03 and -0.14, P < 0.85, respectively). The results indicate the presence of chronic and persistent pulmonary inflammation in stable patients with COPD. Induced sputum permitted the demonstration of the existence of a subpopulation of cells in which neutrophils predominated. The serum concentration of all inflammatory markers did not correlate with the pulmonary functional impairment.